Analysis of Economic Potential in Ogan Komering Ulu Timur Area in Reducing Crime Rate, South Sumatra Province - widia novita lukitasari wa; Roby Cahyadi Kurniawan; Arizka Warganegara; Hertanto Hertanto (Institut Pemerintahan Dalam Negeri, 2023)
To achieve the objectives of regional economic development, development policies based on regional characteristics (endogenous development) are needed by utilizing the potential of local resources. Identification of potential economic sectors is a must to optimize the process and success of the intended economic development. Economic inequality from a functionalist point of view is caused by elements of society that do not carry out their functions optimally. In addition, economic inequality is seen from a conflict perspective that inequality is not a social problem, this is because in society there are different interest groups and fight over existing resources. The solution that can be applied to this phenomenon is that the government can first encourage elements of society to improve their functions in society.